2016
DOI: 10.1177/0969733015626713
|View full text |Cite
|
Sign up to set email alerts
|

Uniforms in dementia care: A barrier or a necessity?

Abstract: This is a case study of an ethical dilemma concerning the appropriateness of encouraging care-staff, working within a dementia care home, to either wear a clinical uniform or not to wear a clinical uniform in practice. It is proposed that people living with dementia may sustain higher levels of wellbeing if care-staff wear clothes that are more akin to their care home environment, for example, wearing similar clothes to the residents or even wearing pyjamas and nightwear during a night shift. The counter argum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Research has shown that when Elders see people in uniforms, they act sicker and more dependent. 17,18,19,20 Rebecca and her team witnessed their residents behaving more independently when the care team began wearing professional attire. The residents were more likely to try to move out to the garden or go into the kitchen for a snack on their own.…”
Section: Uniformsmentioning
confidence: 99%
“…Research has shown that when Elders see people in uniforms, they act sicker and more dependent. 17,18,19,20 Rebecca and her team witnessed their residents behaving more independently when the care team began wearing professional attire. The residents were more likely to try to move out to the garden or go into the kitchen for a snack on their own.…”
Section: Uniformsmentioning
confidence: 99%
“…Some caregivers believe that not wearing a uniform would have a detrimental effect on residents. They think this practice may lead to a greater level of distress due to disorientation and the inability of the resident to identify caregivers when needed (Mitchell, 2018). The questions of hygiene, infection and also financial considerations (cleaning clothes) are further arguments for those against the suppression of uniform.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors have been recognised as important elements in the care of people with dementia (Brawley, 2001). Among these factors, the importance of the caregivers’ appearance and more particularly their street clothes has been raised (Charras & Gzil, 2013; Mitchell, 2018; Newton & Chaney, 1996). Indeed, a nursing home is not a hospital and residents should feel at home.…”
Section: Introductionmentioning
confidence: 99%